Aluminum alloy and preparation method thereof

By adding specific elements to aluminum alloys and using selective laser melting and annealing processes, the problem of strength reduction of aluminum alloys at high temperatures is solved, and high strength and high density of aluminum alloys under high temperature conditions are achieved.

CN119351828APending Publication Date: 2025-01-24INSTITUTE OF MATERIALS & INTELLIGENT MANUFACTURING JIANGXI ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411463577.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When existing aluminum alloys are in service at high temperature, the grains grow and the reinforcement phases are coarser, resulting in a sharp drop in the high temperature strength, making it difficult to meet the engineering application needs of high temperature (greater than 300℃).

Method used

By adding FE, Mn, CE, ZR, ER, and Y to the aluminum alloy, overrive solid solution and enhanced phase are formed, such as Al13Fe4 and Al6MN, which improves the high temperature intensity of aluminum alloy. The molten laser of the constituency and the annealing treatment process is used to ensure the uniform distribution of the elements and the fineness of grains.

Benefits of technology

It significantly improves the high temperature strength and density of aluminum alloy. The tensile strength of the room temperature reaches 590 to 620MPa, and the extension rate is 0.6 to 0.9 %. When serving at 400 ° C, the tensile strength is 170-255MPa, and the extension rate is 16.2 to 22.5 %. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351828A_ABST
    Figure CN119351828A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum alloy and a preparation method thereof, and belongs to the technical field of aluminum alloys. The aluminum alloy provided by the invention comprises the following chemical components in percentage by mass: 4.0 to 10.0 percent of Fe, 1.0 to 3.5 percent of Mn, 0.3 to 1.2 percent of M1, 0.3 to 0.75 percent of M2 and the balance of Al, m1 comprises at least one of Ce and Zr; m2 comprises at least one of Er and Y. Fe, Mn and M1 can be subjected to solid solution in an aluminum matrix to form a supersaturated solid solution, and the solid solution strengthening effect is achieved; fe and Mn are beneficial to formation of strengthening phases such as a quasicrystal phase and high-temperature-resistant particles Al13Fe4 and Al6Mn, and high strength is achieved at the high temperature; er and Y can achieve the effects of grain refining and phase strengthening, a small amount of Er and Y are dissolved in an aluminum matrix in a supersaturated solid solution mode, most of Er and Y are enriched at the grain boundary, and therefore the high-temperature strength is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloys, and particularly relates to an aluminum alloy and a preparation method thereof. Background Art

[0002] Aluminum alloy is a material with excellent high temperature performance and has broad application prospects in aviation, aerospace, automobiles and other fields. It can still maintain excellent mechanical properties in high temperature environments.

[0003] At present, aluminum alloys such as Al-Fe alloys are mainly prepared by adding an appropriate amount of Cr, which generates Al on the subgrain boundaries or in the grains of the matrix. 13 Cr2 precipitated phase particles greatly improve the high temperature strength of aluminum alloys, but their high temperature service range is below 200°C. When the service temperature is higher than 200°C, the grains will grow, the strengthening phase will coarsen, and the high temperature strength will drop sharply, making it difficult to meet the requirements of high temperature (greater than 300°C) engineering applications. Therefore, how to improve the high temperature strength of aluminum alloys is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0004] The purpose of the present invention is to provide an aluminum alloy and a preparation method thereof. The aluminum alloy provided by the present invention has excellent high temperature strength.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides an aluminum alloy, the chemical composition of which, in terms of mass percentage, includes: Fe 4.0-10.0%, Mn 1.0-3.5%, M1 0.3-1.2%, M2 0.3-0.75% and the balance Al;

[0007] The M1 includes at least one of Ce and Zr;

[0008] The M2 includes at least one of Er and Y.

[0009] Preferably, the chemical composition includes, by mass percentage, 5.0-8.0% Fe, 2.0-3.0% Mn, 0.3-1.0% M1, 0.4-0.7% M2 and the balance Al.

[0010] Preferably, when the M1 is Ce and Zr, the mass ratio of Ce to Zr is 1:(0.6-1).

[0011] Preferably, when M2 is Er and Y, the mass ratio of Er to Y is (0.2-0.75): 1

[0012] The present invention also provides a method for preparing the aluminum alloy described in the above technical solution, comprising the following steps:

[0013] (1) performing selective laser melting of aluminum alloy powder to obtain a molded product;

[0014] (2) The molded product obtained in step (1) is annealed to obtain an aluminum alloy.

[0015] Preferably, the particle size of the aluminum alloy powder in step (1) is 20 to 70 μm.

[0016] Preferably, the process parameters of the selective laser melting in step (1) include: laser spot diameter 80-130 μm, scanning power 275-400 W, scanning speed 1000-1800 mm / s, laser scanning spacing 0.10-0.15 mm, powder thickness 40-60 μm, and rotation angle between adjacent layers of 0-67°.

[0017] Preferably, the process parameters of the selective laser melting in step (1) include: laser spot diameter 90-120 μm, scanning power 300-350 W, scanning speed 1200-1600 mm / s, laser scanning spacing 0.12-0.14 mm, powder thickness 40-50 μm, and rotation angle between adjacent layers 0-67°.

[0018] Preferably, the holding temperature of the annealing treatment in step (2) is 200-350° C., the holding time of the annealing treatment is 3-10 h, and the rate of heating to the holding temperature is 10-40° C. / min.

[0019] Preferably, the holding temperature of the annealing treatment in the step (2) is 200-300° C., the holding time of the annealing treatment is 5-8 hours, and the rate of heating to the holding temperature is 15-30° C. / min.

[0020] The present invention provides an aluminum alloy, the chemical composition of which includes, by mass percentage, 4.0-10.0% Fe, 1.0-3.5% Mn, 0.3-1.2% M1, 0.3-0.75% M2 and the balance Al; the M1 includes at least one of Ce and Zr; the M2 includes at least one of Er and Y. In the present invention, Fe, Mn and M1 can be dissolved in the aluminum matrix to form a supersaturated solid solution, which plays a role in solid solution strengthening; at the same time, the addition of Fe and Mn helps the quasi-crystalline phase and high temperature resistant particle Al 13The formation of strengthening phases such as Fe4 and Al6Mn provides high strength when in service at room temperature and high temperature; the addition of Er and Y can refine the grains and strengthen the phases, wherein a small amount of Er and Y are dissolved in the aluminum matrix in the form of a supersaturated solid solution, and most of Er and Y are enriched at the grain boundaries, which increases the recrystallization temperature of the aluminum alloy, thereby significantly improving the high-temperature strength of the aluminum alloy, so that the grains of the aluminum alloy will not grow when in service at high temperatures. The experimental results show that the aluminum alloy provided by the present invention has a density of up to 98%, a room temperature tensile strength of 590-620MPa, and an elongation of 0.6-0.9%; when in service at 400°C, the tensile strength is 170-255MPa, and the elongation is 16.2-22.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a morphology diagram of the aluminum alloy powder in Example 2;

[0022] Figure 2 The tensile curves of the aluminum alloy prepared in Example 2 at room temperature and 400°C. DETAILED DESCRIPTION

[0023] The present invention provides an aluminum alloy, the chemical composition of which, in terms of mass percentage, includes: Fe 4.0-10.0%, Mn 1.0-3.5%, M1 0.3-1.2%, M2 0.3-0.75% and the balance Al;

[0024] The M1 includes at least one of Ce and Zr;

[0025] The M2 includes at least one of Er and Y.

[0026] In terms of mass percentage, the aluminum alloy provided by the present invention includes 4.0 to 10.0% Fe. As an embodiment, the mass percentage of Fe in the aluminum alloy can be 5.0 to 8.0%, or 6.0 to 7.0%. In the present invention, Fe can be dissolved in the aluminum matrix to form a supersaturated solid solution, which plays a role in solid solution strengthening; at the same time, the addition of Fe helps the quasi-crystalline phase and high temperature resistant particle Al 13 The formation of strengthening phases such as Fe4 and Al6Mn enables high strength when serving at room temperature and high temperature conditions.

[0027] In terms of mass percentage, the aluminum alloy provided by the present invention also includes 1.0-3.5% Mn. As an embodiment, the mass percentage of Mn in the aluminum alloy can be 2.0-3.0%, or 2.5-3.0%. In the present invention, Mn can be dissolved in the aluminum matrix to form a supersaturated solid solution, which plays a role in solid solution strengthening; at the same time, the addition of Mn helps the quasi-crystalline phase and high temperature resistant particle Al 13The formation of strengthening phases such as Fe4 and Al6Mn enables it to have high strength when serving at room temperature and high temperature conditions. Especially in high-temperature service environments, its high-temperature strength far exceeds that of most 3D printed heat-resistant aluminum alloys, and it can still maintain high strength at 400°C.

[0028] In terms of mass percentage, the aluminum alloy provided by the present invention further includes M10.3-1.2%; the M1 includes at least one of Ce and Zr. As an embodiment, the mass percentage of M1 in the aluminum alloy can be 0.3-1.0%, 0.5-0.8%, or 0.7%. In the present invention, the Ce and Zr can be dissolved in the aluminum matrix to form a supersaturated solid solution, which plays a role in solid solution strengthening.

[0029] In the present invention, when the M1 is Ce and Zr, the mass ratio of Ce to Zr is preferably 1:(0.6-1). As an embodiment, the mass ratio of Ce to Zr may be 1:0.6, 1:0.7, 1:0.8 or 1:0.9. The present invention limits the mass ratio of Ce to Zr to the above range, which can further improve the solid solution strengthening effect.

[0030] In terms of mass percentage, the aluminum alloy provided by the present invention also includes M20.3-0.75%; the M2 includes at least one of Er and Y. As an embodiment, the mass percentage of M2 in the aluminum alloy can be 0.4-0.7%, and can also be 0.5-0.6%. In the present invention, the addition of Er and Y can have the effect of refining grains and strengthening phases, wherein a small amount of Er and Y are dissolved in the aluminum matrix in the form of a supersaturated solid solution, and most of Er and Y are enriched at the grain boundaries, which increases the recrystallization temperature of the aluminum alloy, thereby significantly improving the high temperature strength of the aluminum alloy.

[0031] In the present invention, when M2 is Er and Y, the mass ratio of Er to Y is preferably (0.2-0.75): 1. As an embodiment, the mass ratio of Er to Y may be (0.5-0.75): 1. The present invention limits the mass ratio of Er to Y within the above range, which can further improve the high temperature strength of the aluminum alloy.

[0032] The aluminum alloy provided by the present invention further comprises a balance of Al in terms of mass percentage. In the present invention, the Al is a matrix element.

[0033] In the present invention, Fe, Mn and M1 can be dissolved in the aluminum matrix to form a supersaturated solid solution, which plays a role in solid solution strengthening; at the same time, the addition of Fe and Mn helps the quasi-crystalline phase and high temperature resistant particle Al 13The formation of strengthening phases such as Fe4 and Al6Mn enables high strength when in service at room temperature and high temperature conditions; the addition of Er and Y can refine the grains and strengthen the phases. A small amount of Er and Y is dissolved in the aluminum matrix in the form of a supersaturated solid solution, and most of Er and Y are enriched at the grain boundaries, which increases the recrystallization temperature of the aluminum alloy, thereby significantly improving the high temperature strength of the aluminum alloy.

[0034] The present invention also provides a method for preparing the aluminum alloy described in the above technical solution, comprising the following steps:

[0035] (1) performing selective laser melting of aluminum alloy powder to obtain a molded product;

[0036] (2) The molded product obtained in step (1) is annealed to obtain an aluminum alloy.

[0037] The invention performs selective laser melting molding on aluminum alloy powder to obtain a molded product.

[0038] The present invention has no particular limitation on the source of each aluminum alloy powder, and the powder may be prepared using commercially available products or well-known preparation methods known to those skilled in the art.

[0039] In the present invention, the particle size of the aluminum alloy powder is preferably 20 to 70 μm. As an embodiment, the particle size of the aluminum alloy powder may be 20 to 53 μm.

[0040] In the present invention, the process parameters of the selective laser melting molding preferably include: laser spot diameter 80-130 μm, scanning power 275-400 W, scanning speed 1000-1800 mm / s, laser scanning spacing 0.10-0.15 mm, powder thickness 40-60 μm, and rotation angle between adjacent layers 0-67°. In the present invention, limiting the scanning power within the above range can ensure uniform melting of aluminum alloy powder and avoid excessive vaporization; limiting the scanning speed within the above range can avoid insufficient melting or overburning of aluminum alloy powder; limiting the laser scanning spacing, powder thickness and rotation angle between adjacent layers within the above range can ensure tight bonding between layers.

[0041] As an implementation mode, the laser spot diameter can be 90-120μm, or 90-100μm; the scanning power can be 300-350W, or 325-330W; the scanning speed can be 1200-1600mm / s, or 1200-1400mm / s; the laser scanning interval can be 0.12-0.14mm, or 0.13mm; the powder spreading thickness can be 40-50μm, or 40-45μm.

[0042] In the present invention, the selective laser melting forming is preferably carried out in a protective atmosphere; the protective atmosphere is argon or nitrogen; and the oxygen content in the protective atmosphere is preferably less than 100 ppm.

[0043] In the present invention, the cooling rate of the selective laser melting molding is preferably 10 5 ~10 8 K / s. As an embodiment, the cooling rate may be 10 6 The present invention limits the cooling rate within the above range to enable the aluminum alloy to solidify rapidly. Due to the rapid cooling, the low solubility elements are rapidly dissolved in the aluminum matrix to form a supersaturated solid solution, which has the effect of solid solution strengthening; at the same time, it is also helpful for the quasi-crystalline phase and the high temperature resistant particle Al 13 The formation of strengthening phases such as Fe4 and Al6Mn.

[0044] In the present invention, the substrate is preferably preheated before the selective laser melting molding; the preheating temperature is preferably 150-300°C. As an embodiment, the preheating temperature can be 200°C. In the present invention, preheating the substrate can eliminate the residual stress inside the molded product and between the molded product and the substrate.

[0045] After obtaining the molded product, the present invention performs annealing on the molded product to obtain an aluminum alloy. The present invention uses annealing to remove the residual stress of the molded product.

[0046] In the present invention, the holding temperature of the annealing treatment is preferably 200-350°C; the holding time of the annealing treatment is preferably 3-10 hours; the rate of heating to the holding temperature is preferably 10-40°C / min. The present invention limits the holding temperature and time of the annealing treatment to the above ranges to further eliminate residual stress.

[0047] As an implementation mode, the holding temperature of the annealing treatment may be 200-300° C.; the holding time of the annealing treatment may be 5-8 hours; and the rate of heating to the holding temperature may be 15-30° C. / min.

[0048] In the present invention, the cooling method of the annealing treatment is preferably oil cooling. The present invention has no special limitation on the oil cooling method, and the operation well known to those skilled in the art can be adopted.

[0049] The present invention can further improve the density and room temperature and high temperature performance of the aluminum alloy by adopting selective laser melting forming and annealing treatment. The density is as high as 98%, the room temperature tensile strength is 590-620MPa, and the elongation is 0.6-0.9%; when in service at 400°C, the tensile strength is 170-255MPa, and the elongation is 16.2-22.5%.

[0050] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Example 1

[0052] The chemical composition of the aluminum alloy is, by mass percentage, Fe 8.0%, Mn 2.0%, Ce 0.3%, Er 0.3% and the balance Al;

[0053] The preparation method of the aluminum alloy comprises the following steps:

[0054] (1) Industrial pure aluminum, Al-10Fe, Al-5Mn, Al-5Ce and Al-5Er master alloys are respectively mixed in mass percentage, ultrasonic stirring vacuum melting is performed, and high-purity argon gas supersonic atomization powder is used: the melting temperature is 850°C, the pressure in the melting furnace is 0.8MPa, and high-purity argon gas is used as a medium to supersonic gas atomization of metal droplets to obtain more than 95% spherical or quasi-spherical aluminum alloy powder; wherein the power of ultrasonic stirring vacuum melting is 2000W, and the frequency is 40kHz; the particle size of the aluminum alloy powder is 20-53μm;

[0055] (2) The aluminum alloy powder obtained in step (1) is subjected to selective laser melting to obtain a molded product; the process parameters of the selective laser melting are: laser spot diameter 90 μm, scanning power 325 W, scanning speed 1200 mm / s, laser scanning spacing 0.13 mm, powder thickness 40 μm, rotation angle between adjacent layers 67°, cooling rate 10 6 K / s; oxygen content in nitrogen is less than 100ppm; the substrate is preheated before selective laser melting; the preheating temperature is 200℃;

[0056] (3) The molded product obtained in step (2) is annealed at 200° C. for 5 hours, and then oil-cooled to obtain an aluminum alloy with a density of 98.0%; wherein the rate of heating to 200° C. is 10° C. / min.

[0057] Example 2

[0058] The chemical composition of the aluminum alloy is, by mass percentage, Fe 8.0%, Mn 2.5%, Ce 0.6%, Zr 0.6%, Er 0.3%, Y 0.4% and the balance Al;

[0059] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0060] The morphology of the aluminum alloy powder in Example 2 is as follows: Figure 1 shown.

[0061] from Figure 1 It can be seen that the aluminum alloy powder is spherical or quasi-spherical.

[0062] Example 3

[0063] The chemical composition of the aluminum alloy is, by mass percentage, Fe 8.0%, Mn 2.0%, Ce 0.5%, Y 0.4% and the balance Al;

[0064] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0065] Example 4

[0066] The chemical composition of the aluminum alloy is, by mass percentage, Fe 8.0%, Mn 1.0%, Ce 0.5%, Er 0.2%, Y 0.4% and the balance Al;

[0067] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0068] Comparative Example 1

[0069] The chemical composition of the aluminum alloy is, in mass percentage, 2.5% Fe and the balance Al;

[0070] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0071] Comparative Example 2

[0072] The chemical composition of the aluminum alloy is, in mass percentage, 5.5% Fe and the balance Al;

[0073] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0074] Comparative Example 3

[0075] The chemical composition of the aluminum alloy is, by mass percentage, Fe 8.0%, Ce 0.3%, Zr 0.4%, Er 0.2%, Y 0.3% and the balance Al;

[0076] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0077] Comparative Example 4

[0078] The chemical composition of the aluminum alloy is, by mass percentage, Fe 8.0%, Mn 2.5%, Ce 0.1%, Er 0.2%, Y 0.4% and the balance Al;

[0079] The preparation method of the aluminum alloy is the same as that of Example 1, and an aluminum alloy with a density of 98.0% is obtained.

[0080] According to GB / T 4338-2006, a microcomputer-controlled electronic universal testing machine (CX-DS-04 / 5982U1037) was used to perform room temperature and high temperature tensile tests on the aluminum alloys prepared in Examples 1 to 4 and Comparative Examples 1 to 2. The high temperature tensile test method is as follows: firstly, the aluminum alloy is heated at a heating rate of 5°C / min, and when the temperature is heated to 400°C, the temperature is kept for 10 minutes, and a preload force of 30N is applied, and the high temperature tensile rate is set to 1mm / min. The results are shown in Table 1. The tensile curves of the aluminum alloy prepared in Example 2 at room temperature (i.e., original state) and 400°C are as follows: Figure 2 shown.

[0081] Table 1 Room temperature and high temperature performance data of aluminum alloys prepared in Examples 1 to 4 and Comparative Examples 1 to 2

[0082]

[0083] From Table 1 and Figure 2 It can be seen that when the content of M1 is not within the scope of the present invention, the high temperature strength of the aluminum alloy is poor; the room temperature and high temperature strengths of the aluminum alloy without Mn are poor, which can prove that the present invention limits the content of M1 to the scope of the present invention and adds Mn to improve the room temperature and high temperature strengths of the aluminum alloy; the aluminum alloy prepared by the present invention has high strength at room temperature and still has high strength at high temperature, indicating that the aluminum alloy prepared by the present invention has excellent high temperature performance.

[0084] It can be seen from the above embodiments and comparative examples that the aluminum alloy provided by the present invention has excellent high temperature performance.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An aluminum alloy, the chemical composition of which, in terms of mass percentage, comprises: Fe 4.0~10.0%, Mn 1.0~3.5%, M10.3~1.2%, M20.3~0.75% and the balance Al; The M1 includes at least one of Ce and Zr; The M2 includes at least one of Er and Y.

2. The aluminum alloy according to claim 1, characterized in that The chemical composition includes, by mass percentage, 5.0-8.0% Fe, 2.0-3.0% Mn, 0.3-1.0% M1, 0.4-0.7% M2 and the balance Al.

3. The aluminum alloy according to claim 1 or 2, characterized in that: When the M1 is Ce and Zr, the mass ratio of Ce to Zr is 1:(0.6-1).

4. The aluminum alloy according to claim 1 or 2, characterized in that: When the M2 is Er and Y, the mass ratio of Er to Y is (0.2-0.75):

1.

5. The method for preparing the aluminum alloy according to any one of claims 1 to 4, comprising the following steps: (1) performing selective laser melting of aluminum alloy powder to obtain a molded product; (2) The molded product obtained in step (1) is annealed to obtain an aluminum alloy.

6. The preparation method according to claim 5, characterized in that: The particle size of the aluminum alloy powder in step (1) is 20 to 70 μm.

7. The preparation method according to claim 5, characterized in that: The process parameters of the selective laser melting molding in the step (1) include: laser spot diameter 80-130 μm, scanning power 275-400 W, scanning speed 1000-1800 mm / s, laser scanning spacing 0.10-0.15 mm, powder thickness 40-60 μm, and rotation angle between adjacent layers 0-67°.

8. The preparation method according to claim 5 or 7, characterized in that: The process parameters of the selective laser melting molding in the step (1) include: laser spot diameter 90-120 μm, scanning power 300-350 W, scanning speed 1200-1600 mm / s, laser scanning spacing 0.12-0.14 mm, powder thickness 40-50 μm, and rotation angle between adjacent layers 0-67°.

9. The preparation method according to claim 5, characterized in that: The holding temperature of the annealing treatment in the step (2) is 200-350° C., the holding time of the annealing treatment is 3-10 hours, and the rate of heating to the holding temperature is 10-40° C. / min.

10. The preparation method according to claim 5 or 9, characterized in that: The holding temperature of the annealing treatment in the step (2) is 200-300° C., the holding time of the annealing treatment is 5-8 hours, and the rate of heating to the holding temperature is 15-30° C. / min.